Indirect organogenesis and somatic embryogenesis for regeneration of Rauvolfia serpentina L. from root explants (Bangladesh Journal of Botany, 2020)
Highest frequencies (75%) of friable embryogenic nodular calli were recorded from the root explants in the presence of MS + 4.0 mg/l BAP and 4.0 mg/l NAA. In combinations of BAP and NAA 45.4% callus produced direct plantlets formation and 36.3% only from aerial part of shoots. MS medium with 1.0 mg/l BAP and 0.5 mg/l Kn produced compact callus where 13.3% produced direct plantlets formation and 45.7% produced only shoot formation. Well-developed globular somatic embryos were found to form when the callus were cultured more than 6 - 8 weeks on MS with 1.0 mg/l BAP and 0.5 mg/l Kn. After acclimatization the well rooted plantlets were transferred to pot and grown successfully in soil.